77‐3: High‐Performance Smart Window with Haze Enhancement via Micro‐Domains Manipulation on Alignment Surface. Issue 1 (29th May 2019) - Meng, Cuiling; Tseng, Man Chun; Tang, Shu Tuen; Kwok, Hoi Sing
Abstract : In this article, we present a high performance smart window via micro‐domains manipulation on the alignment surface, which dramatically enhances the power‐on haze by 48%. Large‐scale window with ultra‐hazy state switching in less than 3.5 ms is demonstrated.